What Are Ethical Merits and Drawbacks of Viewing "Medical Mysteries" as Human Subject Research? - Doyle, Tom A.; Conboy, Erin (AMA Journal of Ethics, 2025)
Patient-subjects' participation in an Undiagnosed Diseases Network (UDN) protocol can afford access to innovative diagnostic techniques, especially in genomic medicine, which can shorten the time it takes to accurately diagnose a so-called "medical mystery." But UDN research processes can be complex and involve many variables, which can suggest to some patient-subjects that having enrolled in a UDN protocol was not worthwhile. This commentary on a case rife with diagnostic ambiguity offers a dynamic model of consent that can both facilitate prospective UDN patient-subjects' assessment of potential risks and benefits of participating in diagnostic research and be a source of community engagement.